Modeling and simulation of furnace pulse firing improvements using fuzzy control. (June 2017) - Cadena-Ramírez, Alejandro; Favela-Contreras, Antonio; Dieck-Assad, Graciano
Pulse firing offers significant process and productivity benefits, such as improved temperature uniformity and high heat transfer rates to the product load through maximum system turndown and utilizes the system's burners at their most efficient firing rates. However, overshoot and undershoot is unavoidable. To minimize these effects, the system operates the burner at an enhanced turndown rate. Faster cycle rates improve temperature uniformity but reduce equipment lifetime. Therefore, a tradeoff exists between furnace temperature uniformity and the cycle rate used by the pulse firing control. This paper proposes models and simulates an advanced technique that improves temperature uniformity while decreasing the cycle time used by the pulse firing control. This provides reliable, safe furnace operating conditions, thereby extending the lifetime of the equipment. After an analysis of a furnace's combustion system that utilizes the pulse firing method to control the heat demand of the furnace, non-linearities were found in the combustion system. To improve the performance of the temperature control, an error-driven function was coupled to the control strategy to compensate the signal error fed to a proportional–integral–derivative controller. The error-driven function was implemented using a fuzzy system, which improved the temperature uniformity and allowed a 60% duty cycle reduction in comparison with similar combustion systems.